Buttoned up : American armor and the 781st Tank Battalion in World War II - Robeson, Westin Ellis, 1984- (Williams-Ford Texas A&M University military history series, 2017)
Independent tank battalions were small, self-contained armored units attached to larger infantry divisions as necessary during World War II. The United States Army believed this would provide infantry the firepower and protection it needed on an ever-changing battlefield. In Buttoned Up: American Armor and the 781st Tank Battalion in World War II, Westin E. Robeson explores the contribution of American armor to the Allied victory in World War II. Robeson first provides contextual background with a consideration of the history of the tank itself and the development of armor doctrine during the First World War and interwar years. He then addresses the rebirth of American armor in response to the German attacks in Europe. Finally, he focuses on a particular independent tank battalion, the 781st, as a case study of the effectiveness of armor in World War II.Buttoned Up introduces the reader to the application of American armored doctrine and provides a new understanding of the tank as a weapon.